2014
DOI: 10.3390/antibiotics3040617
|View full text |Cite
|
Sign up to set email alerts
|

Killing of Staphylococci by θ-Defensins Involves Membrane Impairment and Activation of Autolytic Enzymes

Abstract: θ-Defensins are cyclic antimicrobial peptides expressed in leukocytes of Old world monkeys. To get insight into their antibacterial mode of action, we studied the activity of RTDs (rhesus macaque θ-defensins) against staphylococci. We found that in contrast to other defensins, RTDs do not interfere with peptidoglycan biosynthesis, but rather induce bacterial lysis in staphylococci by interaction with the bacterial membrane and/or release of cell wall lytic enzymes. Potassium efflux experiments and membrane pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…12 The mechanism of the antibacterial effect of RTD-1 was investigated in studies on S. aureus and E. coli and is attributed to peptide-induced permeabilization/ impairment of the cytoplasmic membrane of both organisms. 11,29 In this study, we evaluated the antibacterial activity of RTD-1 against CF clinical isolates of P. aeruginosa, including isolates with mucoid, MDR and colistin-resistant phenotypes. RTD-1 was bactericidal against a panel of antibiotic-resistant clinical isolates including several strains with phoPQ and/or pmrAB mutations that confer high-level resistance to colistin.…”
Section: Discussionmentioning
confidence: 99%
“…12 The mechanism of the antibacterial effect of RTD-1 was investigated in studies on S. aureus and E. coli and is attributed to peptide-induced permeabilization/ impairment of the cytoplasmic membrane of both organisms. 11,29 In this study, we evaluated the antibacterial activity of RTD-1 against CF clinical isolates of P. aeruginosa, including isolates with mucoid, MDR and colistin-resistant phenotypes. RTD-1 was bactericidal against a panel of antibiotic-resistant clinical isolates including several strains with phoPQ and/or pmrAB mutations that confer high-level resistance to colistin.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting observation pertaining to autolysis was made for another antibiotic class, the theta-defensins. These peptides trigger autolysis by binding LTAs in S. aureus [117]. In this organism, the major autolysin Atl is controlled by an interplay of WTAs and LTAs.…”
Section: Does Daptomycin Form Domains With Fluid Lipid Domains (Rifs)mentioning
confidence: 99%
“…WTAs in the old cell wall repel Atl and force it to the division site, where it binds to LTAs and exerts its autolytic activity to selectively lyse the peptidoglycan crosswall between daughter cells [118,119]. Upon binding to LTA, theta-defensins release Atl causing uncontrolled digestion of cell wall peptidoglycan and thus cell lysis [117]. Considering the findings for daptomycin concerning autolysis [101,102] and LTA A similar behavior was observed for human beta-defensin 1, which was shown to display a low affinity to lipid II, probably mainly due to electrostatic interactions of the positively charged peptide with the negatively charged pyrophosphate group.…”
Section: Does Daptomycin Form Domains With Fluid Lipid Domains (Rifs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have previously reported that defensins have antibacterial, antiviral and ion channel-modulation activities [32][33][34]. Recently, there are many discoveries regarding antiviral defensin polypeptides from scorpions, which may be new candidates for antiviral drug molecules.…”
Section: Discussionmentioning
confidence: 99%